ESTUDO DA VIABILIDADE DE OVOS ESTOCADOS DE Aedes aegypti (DIPTERA: CULICIDAE) - SERRA, Neide Bezerra; NAKAGAKI, Jelly Makoto; FERNANDES, Wedson Desidério; FERNANDES, Magda Freitas (ANAIS DO ENIC, 2018)
-